2000
DOI: 10.2527/2000.7871829x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of graded levels of potato by-products in barley- and corn-based beef feedlot diets: I. Feedlot performance, carcass traits, meat composition, and appearance.

Abstract: To measure effects of diet on feedlot performance, carcass characteristics, and beef appearance, 144 crossbred beef steers (333+/-.44 kg) were allotted within weight block (3) to a randomized complete block design with a 2 x 3 factorial arrangement of dietary treatments. Main effects were grain (barley or corn) and level of potato by-product (PB) (0, 10, or 20% of diet DM). Steers were fed diets containing 83% concentrate (grain plus PB), 10% supplement, and 7% alfalfa on a DM basis for an average of 130 d. Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 37 publications
9
35
1
Order By: Relevance
“…The similar visual score (L*-value) was confirmed by the myoglobin content, a biochemical parameter. The tendency for a higher moisture content of the meat and a higher drip loss does not agree with other experiments (Boucqué et al, 1982;Nelson et al, 2000;Radunz et al, 2003). In conclusion, culled potatoes stimulated intake in finishing BBDM beef cows.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The similar visual score (L*-value) was confirmed by the myoglobin content, a biochemical parameter. The tendency for a higher moisture content of the meat and a higher drip loss does not agree with other experiments (Boucqué et al, 1982;Nelson et al, 2000;Radunz et al, 2003). In conclusion, culled potatoes stimulated intake in finishing BBDM beef cows.…”
Section: Discussioncontrasting
confidence: 60%
“…The increased dressing percentage for cows fed potatoes is in agreement with previous results obtained with BBDM bulls (unpublished data). Most reports dealing with the effect of potato by-products did not mention significant differences for carcass characteristics (Nelson et al, 2000;Radunz et al, 2003). These authors also noted only small differences in meat composition and quality, owing to potato by-products.…”
Section: Discussionmentioning
confidence: 97%
“…Also, there does not appear to be distinct phylogenetic lineages of "ovine" or "bovine" methanogens. Furthermore, although potato by-products and corn-based diets are commonly used in cattle feedlot diets in the United States and Canada (1,15,16), very little is known about the effect, if any, of these two different finishing diets on methanogen diversity. Interestingly, Kocherginskaya et al (13) reported that corn-fed steers displayed more diverse bacterial populations than hay-fed animals.…”
Section: Resultsmentioning
confidence: 99%
“…Milner et al 1995;Owens et al 1995;Beauchemin et al 1997;Nelson et al 2000). This variability can be attributed in part to differences in energy concentration of the diets, CP source and concentration, roughage source and amount, and grain processing.…”
Section: Animal Performancementioning
confidence: 99%